The benthic ecology of some Ria Formosa lagoons, with reference to the potential for production of the gilthead seabream (Sparua aurata L.) - Gamito, Sofia (2016)
Tese de Doutoramento, Ciências Biológicas, Unidade de Ciências e Tecnologia dos Recursos Aquáticos, Universidade do Algarve, 1994